PENGARUH KESEMPATAN PROMOSI KARYAWAN, KOMPETENSI KARYAWAN DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) TERHADAP TURNOVER KARYAWAN DI PT LEN INDUSTRI (PERSERO) - Putri, Elvina Azalia Eka; Muttaqin, Ridlwan; Recky, Recky (JURNAL LENTERA BISNIS, 2026)
The direction of this research is centered on comprehending the magnitude of the influence of Employee Promotion Opportunities, Employee Competence, and Organizational Citizenship Behavior (OCB) on the Employee Turnover level at PT LEN Industri (Persero). The study employed a quantitative method with 80 respondents determined using Slovin’s formula and selected through simple random sampling. A Likert scale was used as the research instrument, and data were analyzed using SPSS 26. The results indicate that Promotion Opportunities have a positive and significant effect on Employee Turnover (β = 0.287; p < 0.05), while Employee Competence (β = 0.200; p > 0.05) and Organizational Citizenship Behavior (OCB) (β = 0.098; p > 0.05) do not show a significant partial effect. Collectively, the three variables simultaneously exert a significant effect on Employee Turnover. The research model explains 48.6% of turnover variation, while 51.4% is influenced by other factors. These findings highlight the importance of promotion opportunities in reducing turnover and provide strategic insights for the company to strengthen career systems, competency development, and employee rewards.